2018
DOI: 10.1111/raq.12288
|View full text |Cite
|
Sign up to set email alerts
|

Influences of immunostimulants on phagocytes in cultured fish: a mini review

Abstract: Lower vertebrates like fish mostly depend on innate immunity as the first line of defence against invading pathogens. One of the defence mechanisms in innate immunity for fish is the use of phagocytic cells such as monocytes, macrophages, neutrophils, mast cells and dendritic cells in fighting pathogens. These cellular cells employ a variety of mechanisms in protecting fish including but not limited to; the use of pattern recognition receptors and antigen presenting cells to detect the presence of pathogens in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…Abarike et al. (2019) reported that Nano‐Se upregulates the pro‐inflammatory cytokines, which help our finding in Figures 1 and 2 that showed the marked upregulation of IL1B and IL8 in O. niloticus and M. cephalus fish that previously treated with Nano‐Se particle. IL‐1β is a pro‐inflammatory cytokine that stimulates the lymphocytes and macrophages against disease (Low et al., 2003).…”
Section: Discussionsupporting
confidence: 88%
“…Abarike et al. (2019) reported that Nano‐Se upregulates the pro‐inflammatory cytokines, which help our finding in Figures 1 and 2 that showed the marked upregulation of IL1B and IL8 in O. niloticus and M. cephalus fish that previously treated with Nano‐Se particle. IL‐1β is a pro‐inflammatory cytokine that stimulates the lymphocytes and macrophages against disease (Low et al., 2003).…”
Section: Discussionsupporting
confidence: 88%
“…Unlike, the expression of SOD was not affected by dietary supplementation of limonene; however, catalase was upregulated (Aanyu et al., 2018). The roles of OEO and/or LEO seems to have immunomodulatory effect and their dietary administration mainly upregulates pro‐inflammatory cytokines (Abarike et al., 2019). A similar result was obtained by (Abdel‐Latif et al., 2020) who found that dietary supplementation of oregano essential oil (15 g/kg) upregulated the relative expression of hepatic interleukin‐1beta ( IL‐1β ) and interleukin‐10 ( IL‐10 ) genes in common carp.…”
Section: Discussionmentioning
confidence: 99%
“…Differential leucocyte counts in the present study were characterized by predominance of lymphocytes in all groups except EB, which showed predominance of monocytes. Monocytes are mostly short lived, undergo daily spontaneous apoptosis and often differentiate into other cells (Abarike et al., 2019), and hence, fish in general shows low monocyte percentage. Total WBC and monocyte percentage in control fish in the present study were similar to an earlier observation (Ighwela et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The present results are in conformity with several earlier reports where dietary administration of different plant extracts has significantly increased total RBCs, haemoglobin and haematocrit levels, total WBCs and monocytes in fish (Reverter et al., 2014). Fish treated with immunostimulants usually show enhanced phagocytic cell activities (Abarike et al., 2019). However, some earlier studies have reported lower haematological indices compared to control after treatment with herbal plant extracts (Gabriel, 2019).…”
Section: Discussionmentioning
confidence: 99%